Hydrodynamics of Energy-Efficient Axial-Flow Cyclones for Environmentally Safe Cleaning of Gas and Dust Emissions - Valery P. Meshalkin; Nicolay A. Martsulevich; Oleg M. Flisyuk; Ilia G. Likhachev; Antony M. Nzioka (Energies, 2023)
We investigated the operation of an axial-flow cyclone as the most promising dust-cleaning equipment based on energy consumption. Numerical solutions were obtained for the gas-solids suspension flow equations in axial flow cyclones with different separation chambers’ geometry using FlowVision software. The chamber’s geometrical features determined the nature of the gas-solids suspension flow, directly affecting the dusty gases’ purification degree. The circulating gas flows and the turbulent “trace” after the swirl generator were found to negatively influence the cyclone efficiency and the hydraulic resistance values. A high chamber height also negatively affected the gas purification since the bulk of dust particles were removed from the gas-solids flow at the initial section. The initial section’s length coincided with the gas-solids suspension’s jet flow zone due to the flow coming off the swirl vanes’ edges. Due to turbulent mixing, the particles’ secondary entrainment and return to the gas flow began to manifest outside this zone. Based on this analysis, it is possible to develop recommendations for choosing the chamber’s geometric parameters, minimizing the influence of the indicated factors. On the basis of this research, it will be possible to ensure cyclones’ high efficiency with significantly lower hydraulic resistance when designing axial-flow cyclones relative to other types of cyclone.